Clopidogrel and modified-release dipyridamole for the prevention of occlusive vascular events (NICE technology appraisal guidance 90). Issue 7 (4th March 2011) - Stewart, Kirsty; Walters, Matthew; Dawson, Jesse
Abstract : The National Institute for Health and Clinical Excellence has recently published an update of technology appraisal guidance 90, first published in 2005, which evaluated the use of clopidogrel and modified-release dipyridamole for the prevention of occlusive vascular events. This article considers the update in detail and discusses the implications for clinical practice.